2008
DOI: 10.1080/02678370802379440
|View full text |Cite
|
Sign up to set email alerts
|

Being engaged at work and detached at home: A week-level study on work engagement, psychological detachment, and affect

Abstract: Although earlier research has shown that work engagement is associated with positive outcomes for the employee and the organization, this paper suggests that employees also need time periods for temporarily disengaging (i.e., psychological detaching) from work. We hypothesized that work engagement and psychological detachment from work during off-job time predict high positive affect and low negative affect and that psychological detachment is particularly important when work engagement is high. Over the cours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
232
0
8

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 296 publications
(251 citation statements)
references
References 79 publications
11
232
0
8
Order By: Relevance
“…A coping strategy that may facilitate resource replenishment is psychological detachment from work during non-work time. Breaks after work might increase levels of vigor (Sonnentag, Mojza, Binnewies, & Scholl, 2008), which in turn decreases the vulnerability of further losses or spiraling. In addition, being mentally away from work enables individuals to take control over their emotional reactions and decrease their levels of anxiety.…”
Section: Resultsmentioning
confidence: 99%
“…A coping strategy that may facilitate resource replenishment is psychological detachment from work during non-work time. Breaks after work might increase levels of vigor (Sonnentag, Mojza, Binnewies, & Scholl, 2008), which in turn decreases the vulnerability of further losses or spiraling. In addition, being mentally away from work enables individuals to take control over their emotional reactions and decrease their levels of anxiety.…”
Section: Resultsmentioning
confidence: 99%
“…Although many researchers explain engagement as a relatively stable, individual difference variable that varies between persons (5,11). Recent research has indicated that the engagement is subject to moderate daylevel fluctuations around an average level (32). Study of the employees from five German organisations suggest that both engagement when being at work and disengagement when being away from work are most beneficial for employees' affective states (32).…”
Section: Work Engagement and Employee Engagementmentioning
confidence: 99%
“…In general, supervisors could stimulate effective detachment from work in several ways: by acting as role models, by showing how detachment can be most effective ; by setting clear guidelines for separating work and non-work life (cf. Sonnentag, Binnewies, Mojza, & Scholl, 2008); and by providing employees with workshops how to adequately detach from work, preferably in a cognitive and emotional way.…”
Section: Implications For Practicementioning
confidence: 99%